PENDIDIKAN MUSLIMAH BERCADAR DI PESANTREN BER-MANHAJ SALAFI DI KOTA METRO - Wahyudin Wahyudin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2018)
The rapid development of the salafi movement in Indonesia is inseparable from their main approach, namely, purification and education. In the realm of education, there is a phenomenon of the emergence of various salafi schools in various regions in Indonesia, including in the city of Metro, Lampung. Two topics related to the Islamic education system in salafi pesantren and the position of women in salafi pesantren were the questions this research was based on. This research was a qualitative-descriptive study. Data collection was done by direct observation, documentation, and in-depth interviews. The results of the study showed that in terms of the teaching method, the salafi pesantrens in Metro city were not too different from the learning systems in other Islamic boarding schools. Meanwhile, for salafi women, Islamic boarding schools provide a special program for women they call tarbiyah al-nisa'.